Logic Programming and Nonmonotonic Reasoning 11th International Conference, LPNMR 2011, Vancouver, Canada, May 16-19, 2011. Proceedings - Delgrande, James P.; Faber, Wolfgang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This volume contains the refereed proceedings of the 11th International Conference on Logic Programming and Nonmonotonic Reasoning, LPNMR 2011, held in May 2011 in Vancouver, Canada. The 16 revised full papers (13 technical papers, 1 application description, and 2 system descriptions) and 26 short papers (16 technical papers, 3 application description, and 7 system descriptions) which were carefully reviewed and selected from numerous submissions, are presented together with 3 invited talks. Being a forum for exchanging ideas on declarative logic programming, nonmonotonic reasoning, and knowledge representation, the conference aims to facilitate interactions between those researchers and practitioners interested in the design and implementation of logic-based programming languages and database systems, and those who work in the area of knowledge representation and nonmonotonic reasoning.
Keywords: Computer science; Computer programming; Software engineering; Computer logic; Mathematical logic; Computer science -- Mathematics; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Discrete Mathematics in Computer Science; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Software Engineering; Programming Techniques; Electronic books